Diversity of Arbuscular Mycorrhizal Fungi under Jabon (Anthocephalus cadamba) Plantation, Madiun, East Java KEANEKARAGAMAN FUNGI MIKORIZA ARBUSKULA DI BAWAH TANAMAN JABON (Anthocephalus cadamba) DI MADIUN, JAWA TIMUR - Sri Wilarso Budi R; Agustina Puspita Dewi (Jurnal Silvikultur Tropika, 2016)
Soil as the affiliation of biotic and an abiotic components that support the living of soil microbe. Plants can grow well when it was supported by the available of soil microbes, one of them was arbuscular mycorrhizal fungi (AMF). AMF is a symbiotic mutualism between fungi and plant roots. AMF found almost 80% of plants kingdom, one of them is jabon (Anthocephalus cadamba). The research purposed to identify the diversity of AMF under the jabon plantation (Durenan dry soil, Sudimoroharjo dry soil and Sudimoroharjo wet soil ex rice field). The soil samples was obtained from three different jabon plantation location. The result of this research showed that there were three genus of AMF e.g. Glomus, Acalauspora and Entrophospora, found in jabon plantation planted in Durenan dry soil and Sudimoroharjo wet soil meanwhile jabon planted in Sudimoroharjo wet soil could only be found 2 genus, such as Glomus and Acalauspora.Key word: arbuscular mycorrhizal fungi, diversity, genus, jabon